Unilateral laryngeal paralysis in a cat - Wong, W.T. (Wiley Blackwell, 1984)
A case of unilateral laryngeal paralysis in a cat is described which presented with signs of nasal discharge and dyspnoea. The condition is compared with laryngeal paralysis as seen in the horse and dog.